How Implicit Beliefs Influence Trust Recovery - Haselhuhn, Michael P.; Schweitzer, Maurice E.; Wood, Alison M. (Psychological Science, 2010)
After a trust violation, some people are quick to forgive, whereas others never trust again. In this report, we identify a key characteristic that moderates trust recovery: implicit beliefs of moral character. Individuals who believe that moral character can change over time ( incremental beliefs) are more likely to trust their counterpart following an apology and trustworthy behavior than are individuals who believe that moral character cannot change ( entity beliefs). We demonstrate that a simple but powerful message can induce either entity or incremental beliefs about moral character.